1999
DOI: 10.1038/19297
|View full text |Cite
|
Sign up to set email alerts
|

Biological response to climate change on a tropical mountain

Abstract: Recent warming has caused changes in species distribution and abundance 1±3 , but the extent of the effects is unclear. Here we investigate whether such changes in highland forests at Monteverde, Costa Rica, are related to the increase in air temperatures that followed a step-like warming of tropical oceans in 1976 (refs 4, 5). Twenty of 50 species of anurans (frogs and toads) in a 30-km 2 study area, including the locally endemic golden toad (Bufo periglenes), disappeared following synchronous population cras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
988
7
44

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,194 publications
(1,081 citation statements)
references
References 25 publications
24
988
7
44
Order By: Relevance
“…In the tropics, plethodontid salamanders reach highest diversity in high‐elevation cloud forests (Wake, Papenfuss, & Lynch, 1992; Wake & Vredenburg, 2008), and clouds affect distribution patterns for species in these communities (Wake et al., 1992). Clouds may provide moisture during critical dry periods, and changes in CBH may be one cause of population declines in tropical cloud forest communities (Pounds, Fogden, & Campbell, 1999; Rovito, Parra‐olea, Vásquez‐Almazán, Papenfuss, & Wake, 2009). We find that in the high‐elevation temperate forests of the Blue Ridge Mountains, the presence of clouds in high‐elevation pockets of talus habitat likewise creates distinct climatic refugia.…”
Section: Discussionmentioning
confidence: 99%
“…In the tropics, plethodontid salamanders reach highest diversity in high‐elevation cloud forests (Wake, Papenfuss, & Lynch, 1992; Wake & Vredenburg, 2008), and clouds affect distribution patterns for species in these communities (Wake et al., 1992). Clouds may provide moisture during critical dry periods, and changes in CBH may be one cause of population declines in tropical cloud forest communities (Pounds, Fogden, & Campbell, 1999; Rovito, Parra‐olea, Vásquez‐Almazán, Papenfuss, & Wake, 2009). We find that in the high‐elevation temperate forests of the Blue Ridge Mountains, the presence of clouds in high‐elevation pockets of talus habitat likewise creates distinct climatic refugia.…”
Section: Discussionmentioning
confidence: 99%
“…Other diseases implicated in recent decimation of amphibian populations include Aeromonas hydrophila, the bacterium responsible for red leg disease (Cunningham et al, 1996) and iridoviruses (Bollinger et al, 1999). Additional stressors include introduced predators or competitors (Corn, 2000), increased temperatures and other deleterious aspects of climate change (Pounds et al, 1999), and increased exposure to UV-B, which has been suggested to reduce reproductive success and survival of amphibians at high altitudes (Blaustein et al, 1994).…”
Section: Malformation and Declining Amphibian Populationsmentioning
confidence: 99%
“…Por outro lado, casos de extinção e declínio populacional de diferentes espécies de anuros foram notados em diferentes continentes (Pechmann & Wilbur 1994, Stebbins & Cohen 1995, Halliday 1998Pounds et al 1999). Na Mata Atlântica, embora tenham sido registrados declínio e desaparecimento de espécies antes abundantes (Heyer et al 1988, Bertoluci & Heyer 1995, Eterovick et al 2005, é extremamente difícil julgar o grau de ameaça às espécies, principalmente frente ao desconhecimento sobre a distribuição, uso de hábitat e biologia das fases larval e adulta das espécies (Young et al 2001).…”
Section: Introductionunclassified